2013
DOI: 10.19154/njwls.v3i1.2520
|View full text |Cite
|
Sign up to set email alerts
|

Engaged or Not? A Comparative Study on Factors Inducing Work Engagement in Call Center and Service Sector Work

Abstract: The aim of this study was to compare the possibilities of experiencing positive well-being in call centers and other service sector work. The article focuses on the prevalence of working conditions (job demands, autonomy, and social support)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
(78 reference statements)
2
20
0
Order By: Relevance
“…An increasing number of empirical studies have demonstrated a positive and predictive relationship between job crafting behaviours and work engagement. In a longitudinal study, Tims, Bakker & Derks, demonstrate that employees who practiced job crafting behaviours in the form of seeking challenges and resources positively changed their work environment, thereby increasing their work engagement and decreasing burnout [28]. In another longitudinal study, Demerouti, Bakker & Gevers find that the more resources individuals seek at work, the more engaged they are in their work [36].…”
Section: The Mediator Effect Of Job Crafting On Work Engagement and Omentioning
confidence: 99%
See 3 more Smart Citations
“…An increasing number of empirical studies have demonstrated a positive and predictive relationship between job crafting behaviours and work engagement. In a longitudinal study, Tims, Bakker & Derks, demonstrate that employees who practiced job crafting behaviours in the form of seeking challenges and resources positively changed their work environment, thereby increasing their work engagement and decreasing burnout [28]. In another longitudinal study, Demerouti, Bakker & Gevers find that the more resources individuals seek at work, the more engaged they are in their work [36].…”
Section: The Mediator Effect Of Job Crafting On Work Engagement and Omentioning
confidence: 99%
“…Job crafting refers to "…the changes that employees may make to balance their job demands and their job resources with their personal abilities and needs" [28]. In broad terms, job crafting complements the traditional approaches to job designwhich involve a top-down perspective whereby management is responsible for designing jobsby recognising the bottom-up role of the proactive employee, and the capabilities with which they can craft their jobs [29].…”
Section: Job Crafting In the Jd-r Model In Outbound Call Centre Operamentioning
confidence: 99%
See 2 more Smart Citations
“…Berg (2013) emphasized that another factor that affects work engagement is perceived by support. Mustosmäki, Anttila & Oinas (2013) stated that decrease in difficulties of jobs and increase in discretionary power is another factor of work engagement. While Arifin et al (2014) implied that organizational culture and transformational leadership are other predictors that determine work engagement Maslach, Schaufeli & Leiter (2001) indicated that harmony between individuals and jobs also influences work engagement.…”
Section: Introductionmentioning
confidence: 99%